Analisis Faktor yang Memengaruhi Volume Ekspor Kopi Sumatera Utara - Josuabrema Barus; I Wayan Sukadana (Jurnal Publikasi Manajemen Informatika, 2025)
Indonesia is one of the largest coffee-exporting countries in the world. This is due to the high competitiveness of Indonesian coffee in the international market, as well as its distinctive characteristics. This study aims to analyze the influence of export prices, exchange rates, and total production on the export volume of Sumatran coffee from 2010 to 2023. The data used in this research is secondary data obtained from literature studies conducted by the Central Bureau of Statistics (BPS), the Ministry of Trade, the Plantation Service, UN COMTRADE, the World Bank Commodity Price Data, as well as related articles and journals. The data consists of time series records spanning from 2010 to 2023. This study employs a non-participant observation method to collect data, which involves reading, gathering, and documenting relevant information. The analysis technique used is multiple linear regression, and data processing is conducted using SPSS software version 27. The results of data processing and simultaneous testing indicate that export prices, exchange rates, and total production influence the export volume of Sumatran coffee during the 2010-2023 period. Partially, export prices and total production have a positive and significant impact on export volume, whereas the exchange rate has a negative and significant effect. To enhance the global competitiveness of Indonesian coffee, efforts to increase its productivity—currently still relatively low—are essential.